Probe measurements of parameters of dense gasmetallic plasma in the inhomogeneous magnetic field of a planar magnetron discharge - Chunadra, А.G.; Sereda, К.N.; Tarasov, I.K. (Вопросы атомной науки и техники, 2018)
The paper presents measurements of the electron temperature and plasma concentration in both stationary and pulsed operation modes of a longitudinal planar MDC with a magnetically insulated anode in stationary and highcurrent pulsed operation modes with a high-voltage impulse voltage addition. The measurements were carried out according to the standard procedure for Langmuir double probes. The obtained volt-ampere characteristics of a double probe show that the electron temperature increases by a factor of two in the pulsed mode of operation of the magnetron in comparison with the steady-state regime, and the density of the pulsed plasma increases by three orders of magnitude.